Implementation of the An-Nahdliyah Method in Improving the Al-Qur'an Reading Skills of Grade VII Students at MTs Darul Ulum Panaragan Jaya - M Hasan Ma’ruf; Nur Saidah; Achmad Hanuji Akbar (FKIP - Universitas Riau, 2026)
This study explores the implementation of the An-Nahdliyah method in enhancing seventh-grade students’ Al-Qur’an reading skills at MTs Darul Ulum Panaragan Jaya. The research was motivated by the varying abilities of students in reading the Qur’an, particularly in fluency, accurate pronunciation of hijaiyah letters, and proper application of tajweed rules. Employing a qualitative case study design, this study aimed to describe the habituation of Qur’an reading activities at school, analyze the implementation of the An-Nahdliyah method during the learning process, and explore its contribution to improving students’ Qur’an reading skills. Data were collected through direct classroom observations, semi-structured interviews with teachers, students, and the school principal, and analysis of relevant school documents. The findings indicate that Qur’an reading activities have become part of the school’s religious culture through routine habituation practices conducted before classroom learning. The An-Nahdliyah method was implemented systematically through rhythmic reading techniques, repeated exercises, teacher modeling, and individualized guidance. These approaches contributed to observable improvements in students’ reading fluency, pronunciation accuracy, tajweed application, and confidence in reading the Qur’an. This study underscores the significance of structured and contextually appropriate methods supported by a supportive religious learning environment in developing students’ Qur’anic literacy within formal madrasah education.